Use of prophylactic oral calcium after total thyroidectomy: a prospective study - Langner,Erwin (2017)
ABSTRACT Objective The aim of this study was to evaluate the use of prophylactic oral calcium after total thyroidectomy in the prevention of symptomatic hypocalcemia, and to develop a rational strategy of oral calcium supplementation following this type of surgery. Subjects and methods Prospective study including 47 patients undergoing total thyroidectomy from January 2007 to February 2012. The patients were allocated to one of the following groups: I (no postoperative calcium) or II (oral calcium 3 g per day). Oral calcium was started at the first postoperative day and administered until the sixth postoperative day. The patients were followed up for a minimum of 6 months and evaluated with a minimum of five measurements of ionized calcium: preoperative, 16 hours after surgery, seventh postoperative day, and at postoperative days 90 (PO90) and 180 (PO180). The cohort included three men and 44 women, of whom 24 (51.9%) had benign thyroid disease, and 23 had suspected or confirmed malignant disease. Results When compared with Group II, Group I had significantly higher rates of postoperative biochemical hypocalcemia at PO1 and PO180, and of symptomatic hypocalcemia at PO1, PO7, and PO90. Other data were not significantly different between the groups. Conclusion We conclude that postoperative calcium supplementation effectively prevents symptomatic and biochemical hypocalcemia after total thyroidectomy, and can be safely used after this procedure. The presented strategy of oral calcium supplementation may be implemented in a viable manner.